Treatment of punched-out atrophic and rolling acne scars in skin phototypes III, IV, and v with variable square pulse erbium:Yttrium-aluminum-garnet laser resurfacing - Rungsima Wanitphakdeedecha (2018)
BACKGROUND Treatment of acne scars remains a challenge, especially in dark-skinned individuals. Treatment parameters may be optimized by selecting appropriate pulse width and laser energy that enhance tissue thermal response with limited morbidity. OBJECTIVE To determine the efficacy and side effects of variable square pulse (VSP) erbium:yttrium-aluminum-garnet (Er:YAG) laser resurfacing for treatment of punched-out atrophic and rolling acne scars. METHODS Twenty-four subjects with acne scars were treated monthly for 2 months with four passes of VSP Er:YAG laser resurfacing using a 7-mm spot size and a fluence of 0.4 J/cm2. Subjects were divided into two groups and treated with two different pulse widths: 300 μs (short pulse, SP) and 1,500 μs (extra-long pulse, XLP). Objective and subjective assessments were obtained at baseline and 1, 2, and 4 months after treatment. RESULTS In the SP group, skin smoothness improved significantly (p<.01); in the XLP group, skin smoothness (p<.05) and scar volume (p<.05) improved significantly from baseline. Adverse effects consisted of transient postinflammatory hyperpigmentation (18%) and acneiform eruption (9%). CONCLUSIONS Low-fluence VSP Er:YAG laser resurfacing is a promising treatment option for acne scars, with minimal risk of side effects. Laser pulse width and energy determine the efficacy and the risk of side effects. © 2009 by the American Society for Dermatologic Surgery, Inc.